The spatiotemporal evolution and influencing factors of carbon emissions in the Yellow River Basin based on nighttime light data - Congqi Wang; Fanghua Wu; Haslindar Ibrahim; Wenting Chang (Humanities & Social Sciences Communications)
Abstract To achieve sustainable ecological development in the contemporary global economy and technology, addressing carbon emissions is imperative. The issue of carbon emissions and their impact on the environment has been the subject of intense scrutiny and debate among academicians worldwide. This investigation investigates the Yellow River Basin in China, a region with substantial industrial development. It analyses the fluctuations in carbon emissions and their influencing factors from 2010 to 2022 using nighttime light data. The spatial clustering features of carbon emissions in the prefecture-level communities of the Yellow River Basin from 2005 to 2022 are verified by the spatial autocorrelation analysis. The Gini coefficient is employed to examine regional disparities in carbon emissions in three distinct ways: total difference, intra-regional difference, and inter-regional difference. Ultimately, the GTWR model is implemented to evaluate the variables that influence carbon emissions within the Yellow River Basin. The results suggest that the Yellow River Basin is characterized by substantial spatial clustering. Shandong Province and Lvliang City are home to high-high clustering cities, while Gansu Province, Shaanxi Province, and Sichuan Province are home to low-low clustering cities. Carbon emissions are increasing annually. In comparison to the Upper, Middle, and Lower Yellow River regions, the disparities in carbon emissions between the Middle and Lower Yellow River regions are somewhat lesser. Intra-regional differences follow the trend of Upper Yellow River > Middle Yellow River > Lower Yellow River. Economic development, industrial structure, scientific advancement, and education level consistently positively impact carbon emissions in the Yellow River Basin. However, financial development has a sustained inhibiting effect on carbon emissions, and infrastructure development initially promotes but eventually inhibits carbon emissions.